Effect of Geographical Indication Information on Consumer Acceptability of Cooked Aromatic Rice - Jarma Arroyo, Sara E. (Foods, 2020)
Geographical indication (GI) labeling is used to represent information about specific geographical origins of target products. This study aimed at determining the impact of GI information on sensory perception and acceptance of cooked aromatic rice samples. Ninety-nine participants evaluated cooked rice samples prepared using each of three aromatic rice varieties both with and without being provided with GI information. Participants rated the acceptance and intensity of the cooked rice samples in terms of appearance, aroma, flavor, texture, and overall liking, and also reported how important the GI information was to them. The results showed that consumers rated the cooked rice samples higher in appearance and overall liking when provided with GI information. Interestingly, participants who valued “state-of-origin” information more highly exhibited increased hedonic ratings of cooked rice samples when provided with GI information, but not when no GI information was given. Participants provided with GI information rated flavor or sweetness intensities of cooked aromatic rice samples closer to just-about-right than those without such information. This study provides empirical evidence about how GI information modulates sensory perception and acceptance of cooked aromatic rice samples. The findings will help rice industry, farmers, and traders better employ GI labeling to increase consumer acceptability of their rice products.